PERAN DAN TANGGUNG JAWAB ORANG TUA TERHADAP PENDIDIKAN ANAK DALAM PERSPEKTIF ISLAM - Mujiyatmi, Mujiyatmi (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
Children are a trust given by God to parents. So that parents have an obligation in children's education. The purpose of this research is to describe the roles and responsibilities of parents towards their children's education in an Islamic perspective. In this paper used the research method of literature review (library research). Primary and secondary data sources come from literature in the form of books and journal articles, data analysis uses content analysis. The results of the study show that parents in their role as educators for their children are role models for children. So that the role of parents is very necessary in children's education, parents are the first teachers for children. The big responsibility of parents in the family is not only to provide for their children, but what is more important in the Islamic view is to provide education for their children.